OPTIMALISASI PERAN DINAS PERHUBUNGAN DALAM MENDORONG MINAT MASYARAKAT MENGGUNAKAN ANGKUTAN KOTA DI BEKASI - Angga Wiryo Tri Utomo; Cucu Sugiarti; Sopyan Resmana (LPPM Universitas Abdurrab, 2025)
This study analyzes the role of the Bekasi City Transportation Agency in enhancing public interest in using urban public transportation. The declining interest of the community, driven by poorly maintained fleets, limited supporting facilities, and traffic congestion, constitutes the central focus. The study aims to identify and examine the agency’s role as a regulator, facilitator, and evaluator in improving the operational system of urban transport to make it more efficient, safe, comfortable, and punctual. Employing a qualitative research method with a single-case study design, this research involved field observations, in-depth interviews, and document analysis to obtain both primary and secondary data. The findings indicate that, as a regulator, the Transportation Agency has actively carried out supervision and licensing functions through vehicle inspections, roadworthiness tests, and the OSS system, despite facing challenges such as low digital literacy among operators, suboptimal fleet conditions, and driver behavior. As a facilitator, the agency has conducted service ethics training and initiated urban transport modernization programs, including route reconfiguration, fleet renewal, and technological integration such as air conditioning, CCTV, and e-money systems, although constrained by budget and policy limitations. Lastly, as an evaluator, the agency has demonstrated a proactive approach by designing technology-based evaluation strategies, including the installation of CCTV and the development of a monitoring center, despite incomplete infrastructure readiness. This continuous evaluation commitment highlights the active role of the Transportation Agency in improving the urban transport system. In conclusion, the role of the transportation agency whether as regulator, facilitator, or evaluator is crucial in addressing challenges and increasing the attractiveness of urban transport in Bekasi, although several obstacles in implementation remain.